The complicated relationship between asthma and swimming - Czarnecka, Karolina; Burda, Katarzyna; Korczak, Anna; Szewczyk, Oliwia; Olek, Ewa; Jędrzejczyk, Justyna; Łopacińska, Olga; Stańczyk, Katarzyna; Korn, Aleksandra; Wójcik, Emilia (Quality in Sport, 2024)
Introduction: Apart from pharmacological treatment, non-pharmacological strategies including physical activity play a significant role in the management of asthma. The aim of this paper is to examine various topics related to swimming and asthma. They include the detailed effect of swimming on asthma control,the potential role of swimming in early childhood asthma development, exercise induced asthma in swimmers as well as the relationship between asthma and cold water swimming. Review methods: This article is based on the literature found in the PubMed Database from the period of 1971-2024 with the use of keywords such as “asthma”, “swimming”, “cold water swimming”, “exercise induced asthma”, “childhood asthma” Description of the state of knowledge: Swimming is a safe form of physical activity for asthma patients.Swimming training enhances aerobic capacity, reduces exercise-induced bronchoconstriction and improves lung function in both pediatric and adult patients. However, there is a concern regarding indoor swimming pools that chlorine can  potentially induce airway inflammation. There is research suggesting that early life swimming pool exposure may contribute to the asthma development in atopic children. There is some premise to the thought that cold water swimming may help alleviate asthma symptoms, but it also carries many risks.Swimming is a major cause of exercise induced asthma in professional athletes. Conclusions: Alongside appropriate pharmacological treatment, swimming is a valuable strategy in asthma management in both pediatric and adult asthma patients. The risks of chlorinating pools are still not known to outweigh the benefits of swimming for asthmatics. Further research should be carried out on safety of early swimming in atopic children. Cold water swimming should also be evaluated in terms of safety and potential benefits for asthma patients.